Understanding Sibling Rivalry: A Psychological Perspective on the Family Dynamics of Yakub in Surah Yusuf - Rahman, Karunia Akbar; Azizah, Alfiyatul (JOURNAL OF QUR'AN AND HADITH STUDIES, 2023)
Sibling rivalry is a common problem in families, often fuelled by a lack of parental affection and feelings of inequality. Gen-Z, who are more sensitive, are more prone to this problem. Many cases in recent times of bullying and mistreatment of siblings. The Qur'an illustrates this phenomenon as a guide with the story of Ya'kub's family in Surah Yusuf. This study aims to understand the factors and consequences of this conflict as well as propose solutions through a psychological approach to overcome it.The results of this study identified four stages of Qur'anic discourse relating to sibling rivalry in Surah Yusuf. From a psychological perspective, preventing competition between siblings can be achieved through internal factors such as fostering a sense of good competition and patience, and external factors such as parents providing justice, care, affection, and not comparing with others.